HEART FAILURE: PHYSIOLOGICAL AND PATHOLOGICAL MECHANISMS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores the physiological and pathological mechanisms underlying heart failure, a condition in which the heart is unable to pump blood effectively to meet the body's needs. The paper discusses the normal functions of the heart, how these functions are compromised in heart failure, and the key contributing factors such as myocardial infarction, hypertension, and cardiomyopathies.